Effects of guided deep breathing on breathlessness and the breathing pattern in chronic obstructive pulmonary disease: A double-blind randomized control study. Issue 2 (February 2015) - Borge, Christine R.; Mengshoel, Anne Marit; Omenaas, Ernst; Moum, Torbjørn; Ekman, Inger; Lein, Martha P.; Mack, Ulrich; Wahl, Astrid K.
Highlights Guided breathing show positive effect on perceived change of breathlessness in COPD. Guided breathing show positive effect on breathing pattern in COPD. All groups (i.e. breathing, music, relaxation) show positive improvement of COPD symptoms. All groups may have an efficacy of self-care approaches.